2012
DOI: 10.2166/wp.2012.213
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Water Poverty Index in border colonias of west Texas

Abstract: This study applied the Water Poverty Index (WPI) in border colonias of west Texas. The colonias are mostly unincorporated communities located primarily in New Mexico and Texas along the border with Mexico and are characterized by high poverty rates and sub-standard living conditions. In Texas, access to drinking water and sanitation services has been identified as one of the most significant determinants of health in over 350 colonias with about 50,000 residents. The WPI is a multidimensional measure that link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 10 publications
0
24
0
Order By: Relevance
“…Results identified the neediest of the studied colonias and showed that improvements in any of the 4 indicators would benefit that community. Results also identified specific needed improvements for the other colonias studied, allowing for more focused community resources [27].…”
Section: Indicators Water Poverty Index Studiesmentioning
confidence: 98%
See 3 more Smart Citations
“…Results identified the neediest of the studied colonias and showed that improvements in any of the 4 indicators would benefit that community. Results also identified specific needed improvements for the other colonias studied, allowing for more focused community resources [27].…”
Section: Indicators Water Poverty Index Studiesmentioning
confidence: 98%
“…Korc and Ford [27] applied the WPI model in 131 households along the border colonias of west Texas. The WPI indicators include:…”
Section: Indicators Water Poverty Index Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Other quantitative assessments have been developed or integrated into composite indices as key indicators of water resource deprivation. These include characteristics related to the ecological services of water systems at watershed, regional, or national scales (Table ) . At the country or basin scale, multiple measures exist to identify thresholds for water‐related risk in terms of hazard, vulnerability, and exposure of water insecurity .…”
Section: Current Measurements and Metricsmentioning
confidence: 99%